2014
DOI: 10.26719/2014.20.6.391
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zinc supplementation in children with asthma: a randomized, placebo-controlled trial in northern Islamic Republic of Iran

Abstract: There are conflicting reports about the benefits of zinc supplements in childhood asthma. This study examined the effect of zinc supplementation in children with asthma attending an outpatient clinic in Sari, Islamic Republic of Iran. In a randomized, double-blind, placebo-controlled clinical trial over 8 weeks, 284 children on inhaled steroids were allocated to receive zinc supplements (50 mg/day) (n = 144) or placebo (n = 140). Cases and controls had low initial serum zinc concentrations [61.8 (SD 7.3) µg/dL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 23 publications
3
27
2
2
Order By: Relevance
“…20 The present study used zinc supplementation on a daily basis but given in lower dosage (30 mg of zinc/day) compared to Ghaffari study. 19 However, we found relatively the same effectiveness in improving clinical symptoms of asthma as in the previous study. The dosage of zinc in this study was approximately 3-4 times of the recommended daily allowances as used for treatment of zinc deficiency.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…20 The present study used zinc supplementation on a daily basis but given in lower dosage (30 mg of zinc/day) compared to Ghaffari study. 19 However, we found relatively the same effectiveness in improving clinical symptoms of asthma as in the previous study. The dosage of zinc in this study was approximately 3-4 times of the recommended daily allowances as used for treatment of zinc deficiency.…”
Section: Discussionsupporting
confidence: 84%
“…18 Ghaffari and colleagues found that the 50 mg zinc supplement in children with asthma attending at outpatient clinic yielded significant improvements in clinical symptoms such as cough, wheezing, dyspnea and pulmonary functions during follow-up. 19 However, Pouramjad and colleagues reported the conflicting results that zinc supplementation by dosage of 50 mg on alternate days did not have any significant beneficial effect on pulmonary function parameters. 20 The present study used zinc supplementation on a daily basis but given in lower dosage (30 mg of zinc/day) compared to Ghaffari study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the randomized placebo-controlled study by Ghaffari et al on 284 pediatric asthma patients, it was reported that when zinc levels significantly increased, improvements were seen in clinical symptoms such as coughing, wheezing and respiratory distress, and clear recovery of the FVC and FEV1 ratios in the group of patients given 50mg/day of zinc for 8 weeks (20). As opposed to some studies (7), our results raise the question that serum zinc levels might not have a significant effect on bronchoconstriction which leads these patients to develop frequent attacks.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Daily supplementation of low dose of zinc was proven to be beneficial at least in terms of reduction in severity of clinical signs and symptoms of bronchial asthma in children. 6 Unlike zinc, the deficiency of magnesium in asthma patients was not found in a clinical study but has shown the weak but significant effects in treatment of acute asthma. 7,8 This perhaps indicates the restricted role of magnesium in the treatment of only severe acute exacerbations of asthma.…”
Section: Introductionmentioning
confidence: 99%